## Simplifying the Expression (x³y)⁶

This article will guide you through simplifying the expression **(x³y)⁶**.

### Understanding the Rules of Exponents

To simplify this expression, we need to understand the following rules of exponents:

**Product of powers:**(a^m) * (a^n) = a^(m+n)**Power of a product:**(ab)^n = a^n * b^n**Power of a power:**(a^m)^n = a^(m*n)

### Applying the Rules to Simplify

**Apply the power of a product rule:**(x³y)⁶ = x³⁶ * y⁶**Apply the power of a power rule:**x³⁶ * y⁶ = (x³)^⁶ * y⁶ = x¹⁸ * y⁶

### The Simplified Expression

Therefore, the simplified form of **(x³y)⁶** is **x¹⁸y⁶**.

### Key Points

- Remember to apply the correct rules of exponents in the right order.
- The simplified expression will have the variables raised to different powers based on the original expression.